The implications of resource dependence for non-profit organisations: the Portuguese case - Macedo, Isabel Maria (2002)
During the last few decades it has been generally accepted that there has been extensive sharing of responsibility between the state and non-profit organisations (NPOs) in order to accomplish public purposes. As a result, the relationship between both sectors, and the degree of dependence of NPOs on the state has been acknowledged as a critical issue within social and public policy debates. However, the intensity of this debate has not been matched by a search for empirical evidence, which might assist in assessing the nature and extent of this dependence as well as the implications, either for the non-profit sector or the state. Therefore this research seeks to address this gap in the literature by providing empirical evaluation of the nature and scope of non-profit organisations dependence on the state for resources regarding the Portuguese case. It also analyses the implications that different types of resource dependencies might have on the perceived autonomy of these organisations and on their organisational and managerial orientations.